A systematic review of risk variables for child abuse material offenders. Issue 2 (31st January 2018) - Garrington, Catherine; Rickwood, Debra; Chamberlain, Peter; P. Boer, Douglas
Abstract : Purpose: The purpose of this paper is to collate the available research into the characteristics of child abuse material (CAM) offenders to inform future assessment and treatment options. This systematic review collates the contribution and directionality of variables from existing research assessing an offenders' use of CAM. Design/methodology/approach: Background and definitions of terminology are reviewed, and a summary of sexual reoffending rates provided. Articles were then identified for inclusion through a systematic review using online searches, EBSCOHost and other databases. Articles were also identified from reference lists. After exclusions, the final sample ( n =17) were reviewed for identified variables and their directional contribution to risk. Findings: Internet only (IO) offenders present with a range of similarities and differences. The demographic, psychological and offence-specific risk variables identified suggest IO offenders differ from other types of sexual offenders. Using the collated variables, IO offender profiles are suggested. Research limitations/implications: Limitations have been identified in the availability of research in this area, the variety of terminology and the definitions in common usage. Additionally, there are challenges in ascertaining the truthfulness of self-reported data. Practical implications: Development of IO offender-specific risk assessment tools would contribute to advances in targeted supervision and treatment. In turn, this contributes to community safety by protecting children from online sexual victimisation. Originality/value: Based on identified gaps, this review contributes to ongoing research by signalling future pathways for IO offender-specific risk assessment.